AB0422 Impact of Combination Etanercept-Dmard Induction Therapy in Active Rheumatoid Arthritis: Interim Results of an International Treat-to-Target Study Conducted in Regions with Limited Biologic Access. (9th June 2015) - Pavelka, K.; Akkoç, N.; Al-Maini, M.; Zerbini, C.A.; Bao, C.; Karateev, D.E.; Nasonov, E.L.; Pedersen, R.; Dinh, A.; Shen, Q.; Vasilescu, R.; Mahgoub, E.; et al.
Abstract : Background: Implementing a treat-to-target (T2T) strategy can require complex therapeutic adjustments to achieve remission or low disease activity (LDA) in rheumatoid arthritis (RA). Management guidelines and evidence from clinical trials with rigid eligibility/treatment protocols may be of limited usefulness in real world practice. Moreover, biologic treatment options have largely been assessed in controlled trials conducted in western Europe and North America. In other geographic regions, biologic therapy is restricted to use only in severe refractory disease, primarily due to cost. Treatment strategies involving biologic dose reduction/withdrawal after patients achieve a targeted response are of special interest in these regions, but few studies have been conducted to date. Objectives: To assess the effects of induction therapy with etanercept 50 mg once weekly (ETN50) plus non-biologic DMARDs in moderate-to-severe RA in Period 1 (P1) of an ongoing T2T study conducted in central/eastern Europe, Latin America, the Middle East, Africa, and Asia. Methods: Eligible patients with DAS28-ESR ≥3.2, either ≥6 TJC+≥6 SJC or ESR ≥28 mm/h, and high-sensitivity C-reactive protein ≥3.5 mg/L despite methotrexate (MTX) therapy (≥10 mg/wk for ≥12 wks) received open-label ETN50+MTX ± other non-biologic DMARDs (hydroxychloroquine, leflunomide, or sulfasalazine) for 24 wks (P1). Dose titration of non-biologic DMARDs and addition/dose increase of oral prednisone was allowed up to wk 16. Patients achieving LDA (DAS28-ESR <3.2) at wk 24 were randomized to ETN50+MTX ± other non-biologic DMARDs or a biologic-free regimen in P2. Results: Among 489 patients treated in P1, mean (SD) age was 47.5 (12.2) y and symptom duration, 8.0 (6.8) y. 72% of patients achieved DAS28-ESR LDA at wk 24 (table ). Adverse events (AEs), serious AEs, serious infections, and AEs leading to dose reduction/discontinuation were reported in 49%, 3%, 1%, and 6% of patients. Conclusions: Induction therapy with etanercept 50 mg+MTX ± other non-biologic DMARDs following a T2T approach was effective in this study of patients with high disease activity. P2 results will determine if initial response has an impact on the efficacy of maintenance therapy with and without biologics. Disclosure of Interest: K. Pavelka Consultant for: Pfizer, MSd, UCB, Roche, BMS, N. Akkoç Grant/research support from: Pfizer, UCB, Consultant for: Abbvie, MSD, Roche, Pfizer, UCB, Speakers bureau: Abbvie, MSD, Pfizer, UCB, M. Al-Maini: None declared, C. A. Zerbini Grant/research support from: Pfizer, Merck, Novartis, Amgen, Lilly, GSK, Consultant for: Lilly, Pfizer, Merck, Servier, Speakers bureau: Lilly, Pfizer, C. Bao: None declared, D. E. Karateev Grant/research support from: Pfizer, BMS, Consultant for: Abbvie, BMS, Celltrion, MSD, Pfizer, Speakers bureau: Company(ies): Abbvie, BMS, Medac, MSD, Pfizer, UCB, E. L. Nasonov: None declared, R. Pedersen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Dinh Consultant for: Pfizer Inc, Q. Shen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Vasilescu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Mahgoub Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Vlahos Shareholder of: Pfizer Inc, Employee of: Pfizer Inc